2015
DOI: 10.1002/pola.27921
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of gradient copolysiloxanes by simultaneous copolymerization of cyclotrisiloxanes and mechanism for kinetics inverse between anionic and cationic ring‐opening polymerization

Abstract: Trifluoropropylmethylsiloxane-phenylmethylsiloxane gradient copolysiloxanes were synthesized by anionic and cationic ring-opening polymerization (ROP) of 1,3,5-tris(trifluoropropylmethyl)cyclotrisiloxane (D during the cationic ROP. AB and BAB type gradient copolymers were obtained because of a difference in the reactivity of the monomers. The microstructure of copolymers was characterized by 29 Si NMR spectroscopy, gel permeation chromatography, and differential scanning calorimetry. Furthermore, the mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 44 publications
(122 reference statements)
0
1
0
Order By: Relevance
“…The universal strategy developed in this study provides a platform for the development of innovative silicone copolymers with controlled structure and performance. Fei H.F. et al [157] obtained trifluoropropylmethylsiloxane-phenylmethylsiloxane gradient copolysiloxanes by copolymerization of 1,3,5-tris(trifluoropropylmethyl)cyclotrisiloxane (D3 F ) and phenylmethylcyclotrisiloxane (DPhrisiloxane) (Figure 38). An analysis of the reactivity ratios showed that the reactivity of D3 F with respect to anionic ROP is higher than that of D3 Ph ; however, D 3 F showed lower reactivity compared to D3 Ph during cationic ROP.…”
Section: Catalytic Rearrangement Reactions For the Preparation Of Pdm...mentioning
confidence: 99%
“…The universal strategy developed in this study provides a platform for the development of innovative silicone copolymers with controlled structure and performance. Fei H.F. et al [157] obtained trifluoropropylmethylsiloxane-phenylmethylsiloxane gradient copolysiloxanes by copolymerization of 1,3,5-tris(trifluoropropylmethyl)cyclotrisiloxane (D3 F ) and phenylmethylcyclotrisiloxane (DPhrisiloxane) (Figure 38). An analysis of the reactivity ratios showed that the reactivity of D3 F with respect to anionic ROP is higher than that of D3 Ph ; however, D 3 F showed lower reactivity compared to D3 Ph during cationic ROP.…”
Section: Catalytic Rearrangement Reactions For the Preparation Of Pdm...mentioning
confidence: 99%